Olfactory event-related potentials (OERPs) and trigeminal event-related potentials (TERPs) in subjects after Covid-19 infection: single-center prospective study - Holý, Richard; Kalfeřt, David; Vašina, Libor; Vorobiov, Oleksii; Dytrych, Petra; Janoušková, Karla; Augste, Eva; Kashiri, Shahriar; Pastorková, Nikola; Mamiňák, Kristýna; Hložek, Jiří; Kovář, Daniel; et al. (Journal of applied biomedicine, 2024)
Olfactory dysfunction (OD) is a common symptom associated with Covid-19. During the Covid-19 pandemic, the importance of psychophysical olfactory tests and electrophysiological olfactory assessment increased. The purpose of the study was to analyze the psychophysical olfactory tests and the post-covid curves of olfactory event-related potentials (OERPs) and trigeminal event-related potentials (TERPs). The prospective study included 98 subjects (62 females / 36 males). The average age was 42 years (range 21-84 years). Group I (n = 77) contained participants who had been infected with Covid-19. They were enrolled in the study at least 1 year after Covid-19. Group II (n = 21) was the healthy normosmic control group. In Group I, the OERPs of 18% participants were absent. Patients in Group I were statistically more likely to have an absence of OERPs (p = 0.036) than subjects in Group II. We did not detect a statistical difference in amplitudes and latencies of the OERPs between Group I and Group II. In Group I, N1 latency of the TERPs was significantly longer (p = 0.002) than in Group II. The amplitude of the N1-P2 interval of the TERPs was significantly lower (p = 0.025) in Group I than in Group II. According to the psychophysical Sniffin stick identification test, hyposmia was detected in 39% in Group I versus 0% in the control Group II. OD is a common post-covid symptom. The presence of OERPs is a significant prognostic factor for olfactory function after Covid 19. We detected a lower percentage of absence of OERPs after Covid-19 compared to the previously published studies of post-viral OD and post-infectious OD. For TERPs, we detected a longer N1 latency and a lower amplitude for the N1-P2 interval after Covid-19. OERPs and TERPs can be considered valid biomarkers to evaluate the progress of post-covid OD.